2001
DOI: 10.1097/00041444-200103000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor trinucleotide repeat polymorphism and personality traits

Abstract: Human family and twin studies have established considerable heritable components influencing individual differences in personality traits as assessed by self-report questionnaires. We have investigated a trinucleotide repeat polymorphism in the androgen receptor gene and personality traits. Healthy Swedish subjects (n = 335) were assessed with the Karolinska Scales of Personality inventory. There were tendencies (P > or = 0.006) in some scales indicating possible relationships between the androgen receptor all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 19 publications
1
46
2
1
Order By: Relevance
“…25 In the case of five studies, correspondence with the authors indicated that it would not be possible to include their data in the metaanalysis. [26][27][28][29][30] In one case, the ethical approval granted to the study did not allow the data to be released 31 and in one case there was no response from the authors. 32 For each study, the following data were extracted: Data were extracted separately for papers where data on more than one gene, or more than one personality scale, were reported.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In the case of five studies, correspondence with the authors indicated that it would not be possible to include their data in the metaanalysis. [26][27][28][29][30] In one case, the ethical approval granted to the study did not allow the data to be released 31 and in one case there was no response from the authors. 32 For each study, the following data were extracted: Data were extracted separately for papers where data on more than one gene, or more than one personality scale, were reported.…”
Section: Data Extractionmentioning
confidence: 99%
“…[7][8][9][11][12][13][14][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The characteristics of the studies are described in Table 1. Of these studies, 33 were not included in the metaanalysis.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…5,30,31 The KSP consists of 135 items forming 15 subscales and measuring relatively stable personality traits. These subscales are often classified into four factors covering different dimensions of temperament: 'neuroticism', 'psychoticism', non-conformity', and 'extraversion'.…”
Section: Personality Assessmentmentioning
confidence: 99%
“…These subscales are often classified into four factors covering different dimensions of temperament: 'neuroticism', 'psychoticism', non-conformity', and 'extraversion'. [31][32][33] Inter-individual variations in several of the KSP scales have been shown to be partly heritable. 2 All KSP personality test scores were standardized using normative data to have an expected mean7SD of 50710 ( ¼ T-scores).…”
Section: Personality Assessmentmentioning
confidence: 99%
“…It was reasonable that male dogs possessing a short CAG repeat, whose AR responsivity is assumed to be increased according to human studies, had higher aggressiveness scores than dogs with relatively long alleles. These data broaden our knowledge about the influence of the AR gene on men's behaviour [8,12,13] by providing a valid animal model. No evidence was found for a relationship between AR gene variants and personality in female dogs.…”
Section: Discussionmentioning
confidence: 70%